THE PRODUCTION OF COMPLEX PROFILE DETAILS BY COMBINED METHOD OF LOST-WAX CASTING AND OF CONSUMABLE PATTERN MODELS - O. I. Shinsky; I. I. Maksyuta; Yu. G. Kvasnitskaya; E. V. Mikhnyan; A. V. Neyma (Литьë и металлургия)
The technological process of receiving figurine castings of a heat resisting alloy HN57KTVYuMBL brand developed and tested by authors a combined method of oflost-wax casting (pouring gate system) and of consumable expanded polystyrene pattern in shell forms kompleks modify ceramics promotes decrease in crack formation of forms at the expense of correctly picked up temperature and time mode of annealing of a form with model. Besides this method allows to receive figurine castings with minimization of an allowance for machining of details, to increase their geometrical accuracy and to lower a roughness.